Growing role of S100B protein as a putative therapeutic target for neurological- and nonneurological-disorders. (August 2021) - Michetti, Fabrizio; Di Sante, Gabriele; Clementi, Maria Elisabetta; Sampaolese, Beatrice; Casalbore, Patrizia; Volonté, Cinzia; Romano Spica, Vincenzo; Parnigotto, Pier Paolo; Di Liddo, Rosa; Amadio, Susanna; Ria, Francesco
Highlights: S100B is a calcium-binding protein mainly expressed in astrocytes and in other definite neural and non-neural cell types. S100B represents a consolidated biomarker of neurological disorders and recently is regarded as an active pathogenic factor. In experimental models of neural and non-neural disorders the expression of S100B correlates with the outcome of the disease. This novel scenario proposes S100B as a common therapeutic target for different diseases. Abstract: S100B is a calcium-binding protein mainly expressed by astrocytes, but also localized in other definite neural and extra-neural cell types. While its presence in biological fluids is widely recognized as a reliable biomarker of active injury, growing evidence now indicates that high levels of S100B are suggestive of pathogenic processes in different neural, but also extra-neural, disorders. Indeed, modulation of S100B levels correlates with the occurrence of clinical and/or toxic parameters in experimental models of diseases such as Alzheimer's and Parkinson's diseases, amyotrophic lateral sclerosis, muscular dystrophy, multiple sclerosis, acute neural injury, inflammatory bowel disease, uveal and retinal disorders, obesity, diabetes and cancer, thus directly linking the levels of S100B to pathogenic mechanisms. In general, deletion/inactivation of the protein causes the improvement of the disease, whereas its over-expression/administration induces a worse clinical presentation. This scenario reasonably proposes S100B as a common therapeutic target for several different disorders, also offering new clues to individuate possible unexpected connections among these diseases.